Impact of Elevated CO2 on Seed Quality of Soybean at the Fresh Edible and Mature Stages - Li, Yansheng; Yu, Zhenhua; Jin, Jian; Zhang, Qiuying; Wang, Guanghua; Liu, Changkai; Wu, Junjiang; Wang, Cheng; Liu, Xiaobing (Frontiers in Plant Science, 2018)
Although the effect of elevated CO2 (eCO2) on soybean yield has been well documented, few studies have addressed seed quality, particularly at the fresh edible (R6) and maturity stages (R8). Under the current global scenario of increasing CO2 levels, this potentially threatens the nutritional content and quality of food crops. Using four soybean cultivars, we assessed the effects of eCO2 on the concentration of crude protein, crude oil, and isoflavones, and analyzed changes in free amino acids, fatty acids, and mineral elements in seeds. At R6, eCO2 had no influence on soybean seed protein and oil concentrations. At R8, eCO2 significantly decreased seed protein concentration but increased seed oil concentration; it also significantly decreased total free amino acid concentration. However, at the same stage, the proportion of oleic acid (18:1) among fatty acids increased in response to eCO2 in the cultivars Zhongke-maodou 2 (ZK-2) and Zhongke-maodou 3 (ZK-3), and a similar trend was found for linoleic acid (18:2) in Zhongke-maodou 1 (ZK-1) and Hei-maodou (HD). Total isoﬂavone concentration increased significantly at both the R6 and R8 stages in response to eCO2. Compared to ambient CO2, the K, Ca, Mg, P and S concentration increased significantly under eCO2 at R6, while the Fe concentration decreased significantly. The response of Zn and Mn concentrations to eCO2 varied among cultivars. At R8 and under eCO2, Mg, S and Ca concentrations increased significantly, while Zn and Fe concentrations decreased significantly. These findings suggest that eCO2 is likely to benefit the accumulation of seed fat and isoﬂavone, but not that of protein. In this study, the response of seed mineral nutrients to eCO2 varied between cultivars.